Overall and abdominal obesity and prostate cancer risk in a West African population: An analysis of the Ghana Prostate Study - Yeboah, E.D.; Hurwitz, L.M.; Biritwum, R.B.; Tettey, Y.; Adjei, A.A.; Mensah, J.E.; Tay, E.; Okyne, V.; Truelove, A.; Kelly, S.P.; Zhou, C.K.; Butler, E.N.; et al. (International Journal of Cancer, 2020)
Obesity has been associated with an increased risk of advanced prostate cancer. However, most studies have been conducted among North American and European populations. Prostate cancer mortality appears elevated in West Africa, yet risk factors for prostate cancer in this region are unknown. We thus examined the relationship between obesity and prostate cancer using a case-control study conducted in Accra, Ghana in 2004 to 2012. Cases and controls were drawn from a populationbased sample of 1037 men screened for prostate cancer, yielding 73 cases and 964 controls. An additional 493 incident cases were recruited from the Korle-Bu Teaching Hospital. Anthropometric measurements were taken at enrollment. We used logistic regression to estimate odds ratios (ORs) and 95% confidence intervals (CIs) for associations between body mass index (BMI), waist circumference (WC), waist-hip ratio (WHR) and prostate cancer, adjusting for potential confounders. The mean BMI was 25.1 kg/m2 for cases and 24.3 kg/m2 for controls. After adjustment, men with BMI ≥ 30 kg/m2 had an increased risk of prostate cancer relative to men with BMI < 25 kg/m2 (OR 1.86, 95% CI 1.11-3.13). Elevated WC (OR 1.76, 95% CI 1.24-2.51) and WHR (OR 1.46, 95% CI 0.99-2.16) were also associated with prostate cancer. Associations were not modified by smoking status and were evident for low- and high-grade disease. These findings indicate that overall and abdominal obesity are positively associated with prostate cancer among men in Ghana, implicating obesity as a potentially modifiable risk factor for prostate cancer in this region.
Research Article
Keywords: body-mass index; obesity; prostate cancer; West Africa